The Influence of Tax Morale, Social Norms, and Trust in Government on Individual Taxpayer Compliance - Gusti Agung Diah Priyam Pradnyandari; Edy Sujana; Anantawikrama Tungga Atmadja (Jurnal Riset Perpajakan: Amnesty, 2026)
Taxpayer compliance remains a crucial issue in public finance because tax revenues constitute a primary source of government funding used to support public services and national development. However, maintaining voluntary taxpayer compliance continues to be a challenge, particularly in developing countries where behavioral factors may significantly influence taxpayers’ decisions. This study aims to examine the influence of tax morale, social norms, and trust in government on individual taxpayer compliance. The research employs a quantitative approach using a cross-sectional survey design. Primary data were collected from 100 individual taxpayers through a structured questionnaire distributed via an online survey. The data were analyzed using multiple linear regression with the assistance of IBM SPSS software. Prior to hypothesis testing, validity, reliability, and classical assumption tests were conducted to ensure the robustness of the regression model. The results indicate that tax morale, social norms, and trust in government have positive and statistically significant effects on taxpayer compliance. Among these variables, trust in government demonstrates the strongest influence on compliance behavior. These findings support the Slippery Slope Framework, which suggests that taxpayer compliance is shaped not only by enforcement mechanisms but also by behavioral and institutional factors. The study contributes to the literature on behavioral taxation by highlighting the importance of moral motivation, social influence, and institutional trust in encouraging voluntary taxpayer compliance.